ESTETIKA PROFETIK AHMAD TOHARI DALAM KHAZANAH BUDAYA CABLAKA - Teguh Trianton (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This article describes the prophetic aesthetic representation inBanyumas culture which is known as cablaka. The data are taken fromliterature review of short stories entitled Senyum Karyamin by AhmadTohari. The work is based on the writer’s background as a cultural observer,and pesantren owner. Hermeunetic approach is applied in this research.Overall the prophetic aesthetic is represented in four characters;cablaka, sabar lan nrima, berjiwa ksatria, dan cancudan. There are threeconcepts of prophetic aesthetic; humanism (amar ma’ruf), liberation (nahimunkar) and transcendence (faith to God, tu’minuna billah).